Immunotherapy for Prostate Cancer: Lessons from Responses to Tumor-Associated Antigens - Westdorp, Harm; Sköld, Annette E.; Snijer, Berit A.; Franik, Sebastian; Mulder, Sasja F.; Major, Pierre P.; Foley, Ronan; Gerritsen, Winald R.; de Vries, I. Jolanda M. (Frontiers in Immunology, 2014)
Prostate cancer is the most common cancer in men and the second most common cause of cancer-related death in men. In recent years, novel therapeutic options for prostate cancer have been developed and studied extensively in clinical trials. Sipuleucel-T is the first cell-based immunotherapeutic vaccine for treatment of cancer. This vaccine consists of autologous mononuclear cells stimulated and loaded with an immunostimulatory fusion protein containing the prostate tumor antigen prostate acid posphatase. The choice of antigen might be key for the efficiency of cell-based immunotherapy. Depending on the treatment strategy, target antigens should be immunogenic, abundantly expressed by tumor cells, and preferably functionally important for the tumor to prevent loss of antigen expression. Autoimmune responses have been reported against several antigens expressed in the prostate, indicating that prostate cancer is a suitable target for immunotherapy. In this review, we will discuss prostate cancer antigens that exhibit immunogenic features and/or have been targeted in immunotherapeutic settings with promising results, and we highlight the hurdles and opportunities for cancer immunotherapy.